Yolk Sac Tumor of the Cervix in an Infant: A Surgical Dilemma - Swati Narasimhan; Janani Arul; Rajendran Swaminathan; Prakash Agarwal (Wolters Kluwer Medknow Publications, 2022)
A 5-month-old child presented with vaginal bleeding and found yolk sac tumor of the uterine cervix. She attained complete remission only with chemotherapy and on follow-up for more than a year. We report this for the unusual age and feasibility of avoiding surgery in selected cases.